All‐in‐One Porous Polymer Adsorbents with Excellent Environmental Chemosensory Responsivity, Visual Detectivity, Superfast Adsorption, and Easy Regeneration. Issue 16 (6th March 2019) - Xie, Yiming; Huang, Wen; Zheng, Bingna; Li, Shimei; Liu, Qiantong; Chen, Zirun; Mai, Weicong; Fu, Ruowen; Wu, Dingcai
Abstract: It remains a formidable challenge to construct advanced adsorbents with superb adsorption, environmental stimuli response, and real‐time detection capability for efficiently treating contaminants from complex environmental systems. A novel class of an all‐in‐one microporous adsorbent that simultaneously has excellent environmental chemosensory responsivity, visual detectivity, superfast micropollutant adsorption, as well as easy regeneration is reported herein. The advanced microporous adsorbent discussed in this study presents a hairy nanospherical morphology composed of a hairy stimuli‐responsive polymeric shell and a shell‐assisted superadsorptive microporous core. The adsorbent not only exhibits a valuable capability of pollutant detection by visible fluorescence quenching, but can also remove organic micropollutants from polluted water with super‐rapid speed (79%, 98%, and 100% of its equilibrium uptake in 7 s, 10 s, and 2 min, respectively) and excellent recyclability (>96%). More importantly, the adsorbent still shows unimpeded adsorption performance in the flow‐through adsorption tests (15 mL min −1 ), indicating a very appealing application prospect. Abstract : An advanced adsorbent with superadsorption, environmental stimuli response, and real‐time detection capability is designed and fabricated to efficiently treat polluted water. The adsorbent presents a hairy microporous nanospherical morphology, emits pH‐dependent blue/a white fluorescence, enables visible detection and superfast removal of micropollutants, exhibits excellent flow‐through adsorption performance, and demonstrates high regeneration efficiency.